Physiological and morphological changes in autolyzing Aspergillus nidulans cultures - Emri, T; Molnár, Z; Pusztahelyi, T; Pócsi, I (Folia microbiologica, 2004)
Physiological and morphological changes in carbon-limited autolyzing cultures of Aspergillus nidulans were described. The carbon starvation arrested conidiation while the formation of filamentous and "yeast-like" hyphal fragments with profoundly altered metabolism enabled the fungus to survive the nutritional stress. The morphological and physiological stress responses, which maintained the cellular integrity of surviving hyphal fragments at the expense of autolyzing cells, were highly concerted and regulated. Moreover, sublethal concentrations of the protein synthesis inhibitor cycloheximide or the mitochondrial uncoupler 2,4-dinitrophenol completely blocked the autolysis. In accordance with the propositions of the free-radical theory of ageing reactive oxygen species accumulated in the surviving fragments with a concomitant increase in the specific superoxide dismutase activity and a continuous decrease in cell viability. Glutathione was degraded extensively in carbon-starving cells due to the action of gamma-glutamyltranspeptidase, which resulted in a glutathione-glutathione disulfide redox imbalance during autolysis.
Keywords: autolýza; glukoneogeneze; Gluconeogenesis; Morphogenesis; morfogeneze; Aspergillus nidulans; glutathion; Carbon; uhlík; Glutathione; Autolysis